The sum of d and 67 is equal to f. Let f = 83. Which equation can be used to find the value of d? A. d = 83 + 67 B. d + 67 = 83 C. d – 83 = 67 D. d – 67 = 83

QUESTION POSTED AT 16/04/2020 - 06:04 PM

Answered by admin AT 16/04/2020 - 06:04 PM

We have this equation:
d+67=f
Now, let f=83, so
d+67=83
Subtract 67 for both side
d+67-67=83-67
d=16
As a result, B. d + 67 = 83 is the correct answer. Hope it help!
Post your answer

Related questions

Find the six arithmetic means between 1 and 29.

QUESTION POSTED AT 02/06/2020 - 01:36 AM

How do you factor the second equation?

QUESTION POSTED AT 02/06/2020 - 01:31 AM

Is (1,-4) a solution to the equation y=-2x

QUESTION POSTED AT 01/06/2020 - 05:03 PM

Three-sevenths of a number is 21. Find the number

QUESTION POSTED AT 01/06/2020 - 04:54 PM